2010
DOI: 10.1111/j.1420-9101.2010.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inbreeding on aversive learning in Drosophila

Abstract: Inbreeding adversely affects life history traits as well as various other fitness‐related traits, but its effect on cognitive traits remains largely unexplored, despite their importance to fitness of many animals under natural conditions. We studied the effects of inbreeding on aversive learning (avoidance of an odour previously associated with mechanical shock) in multiple inbred lines of Drosophila melanogaster derived from a natural population through up to 12 generations of sib mating. Whereas the strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 89 publications
(158 reference statements)
1
38
1
Order By: Relevance
“…One might predict that a complex behavior would be especially susceptible to inbreeding depression because phenotypic variation in behavior is commonly determined by nonadditive genetic effects, with strong dominance and/or epistasis (Meffert et al 2002, Mackay 2009). However, Nepoux et al (2010) found that moderate inbreeding (F ϭ 0.375) in Drosophila had no effect on two behavioral traits, aversive learning or odor responsiveness, even though it was sufÞcient to reduce egg-to-adult viability. They speculated that the absence of inbreeding depression for learning was a consequence of mostly additive-genetic variation and stabilizing selection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One might predict that a complex behavior would be especially susceptible to inbreeding depression because phenotypic variation in behavior is commonly determined by nonadditive genetic effects, with strong dominance and/or epistasis (Meffert et al 2002, Mackay 2009). However, Nepoux et al (2010) found that moderate inbreeding (F ϭ 0.375) in Drosophila had no effect on two behavioral traits, aversive learning or odor responsiveness, even though it was sufÞcient to reduce egg-to-adult viability. They speculated that the absence of inbreeding depression for learning was a consequence of mostly additive-genetic variation and stabilizing selection.…”
Section: Discussionmentioning
confidence: 96%
“…They found no consistent decline in egg dispersion among four inbred lines, although there was considerable variation among lines. Their experimental design could not rule out a confounding effect of purging, however, in which the serial inbreeding used to generate inbred lines selectively eliminates deleterious recessive alleles from the population (see Nepoux et al 2010). As a consequence, the genetic load (and thus the estimate of inbreeding depression) in the test generation may have substantially underestimated the genetic load present in the initial outbred population.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of Drosophila melanogaster , inbred flies were less responsive to training to avoid certain odors than outbred ones and this effect may have arisen from reduced olfactory ability (Nepoux et al 2010). If females that are less perceptive make faster decisions the trend in the time taken for inbred and outbred females to choose is consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Bleakley et al 2006;Mariette et al 2006) and invertebrates (e.g. Nepoux et al 2010;Stone 2012) have been playing an increasingly important role in revealing genetic mechanisms of biological phenomena (Bleakley et al 2006). Despite a number of publications on inbreeding depression in immune (Coffaro & Hinegardner 1977), morphological, and physiological traits (Harada et al 2008), to our knowledge, no information is available on the effects of inbreeding on behaviors of sea urchins.…”
Section: Introductionmentioning
confidence: 96%